Pengaruh Perputaran Kas, Perputaran Piutang dan Modal Kerja terhadap Kinerja Keuangan pada Perusahaan Pertambangan di Bursa Efek Indonesia - Nurfazilah, Nurfazilah Nurfazilah; Zulfan, Zulfan Zulfan; Darmawati, Darmawati Darmawati; Jummaini, Jummaini Jummaini (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
This thesis examines the influence of cash turnover, accounts receivable turnover, working capital on financial performance in mining sector companies listed on the Indonesia Stock Exchange in 2020-2022, which aims to determine the influence of cash turnover, turnover, working capital on Return On Equity (ROE). in mining sector companies listed on the Indonesian Stock Exchange (BEI). The research method used uses quantitative research methods, with multiple linear analysis techniques. The research results concluded that the Cash Turnover and Net Working Capital variables partially had a significant effect on Return On Equity in Mining Sector Companies listed on the Indonesian Stock Exchange Index (BEI) for 2020-2022, while the Receivable Turnover variable partially did not have a significant effect on Return on Equity in mining sector companies listed on the Indonesian Stock Exchange (BEI) Index for 2020-2022 Keywords: Cash turnover, Receivable Turnover, Working Capital, ROE